Comparação entre métodos de extração do óleo de mauritia flexuosa l.f. (arecaceae - buriti) para o uso sustentável na reserva de desenvolvimento tupé: rendimento e atividade antimicrobiana - Carvalho, Cecília Oliveira de (2011)
The economical valorization of some extracted vegetable oils of fruits raisin for the technological improvement of a productive chain that it involves: the cultivation, the extraction of the oils and the characterization of their properties that favor to the interests of the industries that work with these products. The buriti (Mauritia flexuosa L.f.) it is a palm tree whose fruit is a source of rich food in vitamin THE, B and C, it still supplies calcium, iron and proteins. The extracted oil of the fruit is rich in carotene and he/she has medicinal value. In reason of their properties and of their chemical representatives he/she intended in that study to extract for three methods, craft, prensagem and solvent, the buriti oil, characterizing them through the physiochemical properties and accomplishing tests antimicrobianos. The activity antimicrobiana of the oils was evaluated through the diffusion tests in plate and in broth, front to the stumps of reference of the collection of Fiocruz Staphylococcus aureus CBAM 324, Pseudomonas aeruginosa CBAM 232, Escherichia coli CBAM 02, Klebsiella pneumoniae CBAM 382 and Cândida albicans CFAM 1285. As for the efficiency of the extraction of the oil, the hydraulic prensagem, for not using energy and solvents, to have a time of smaller extraction, and for being more economical, it was quite satisfactory presenting a very close income to the presented by the method by solvent and very superior to the craft process. Independent of the adopted methodology it was observed that there were not alterations in the physiochemical parameters of the oils, legitimating the good quality of the same ones. The activity antimicrobiana showed a positive result for the microdiluição method for Staphylococcus aureus and for diffusion in plate with oils diluted for Pseudomonas aeruginosa. This way the use for hydraulic prensagem becomes a source of income the plus, for the rural communities' residents that you/they make the extraction of oils, being considered the possibility of the use of this oil for the pharmaceutical and cosmetic industry in antiseptic formulations